Oxygen saturation probe-related pressure injury prevention in children on an inpatient pediatric unit: a best practice implementation project. Issue 1 (14th March 2023) - Carroll, Amy L.; Palokas, Michelle; Linnell, Shelbi
ABSTRACT: Objectives: The aim of this project was to increase compliance with rotation and documentation of rotation of oxygen saturation probes to reduce medical-device-related pressure injuries in children on a pediatric inpatient unit. Introduction: There are a multitude of factors that place hospitalized children at an increased risk for medical-device-related pressure injuries. Evidence supports the rotation of medical devices, if appropriate, at least twice daily to minimize the risk of medical-device-related pressure injuries in hospitalized children. Methods: The project used JBI's Practical Application of Clinical Evidence System and Getting Research into Practice audit tool for encouraging evidence-based practices. A baseline audit was conducted, followed by the implementation of targeted strategies. The project was completed with a follow-up audit to determine change in practice. Results: The baseline audit revealed significant deficits in two of the seven audit criteria. Barriers to the rotation of oxygen saturation probes and the assessment of skin under oxygen saturation probes were identified by the project team and an electronic health record (EHR) documentation change was implemented. Follow-up audits were not conducted on the five criteria that showed high compliance at baseline. For the remaining two audit criteria, data revealed no improvement in one of the criteria (3% compliance at both baseline and follow-up audits) and an increase from 0% compliance to 43% compliance in the second criterion. Conclusion: Optimizing EHR documentation, specifically ease and efficiency of EHR documentation, has the potential to positively impact clinical practice.